Sosialisasi Dampak Pernikahan Dini Perspektif Pendidikan, Kesehatan Dan Ekonomi Di Desa Pringgabaya Utara - Hadiyani, Baiq; Sulfiana, Baiq; Wahyu Astuti, Ristina; Widia Wati, Via; Hirjan, Muhamad; Haris Zarkasi, Muhammad; Lestari , Sopiana (PELITA NUSA TENGGARA, 2024)
Early marriage is one of the crucial problems experienced by the Indonesian national, especially as NTB The province is the first province for women before the age of 18. So there is a need for cooperation from all agencies in preventing this problem, one of which is by having a comprehensive understanding of the causes and consequences of early marriage as a preventive measure for this problem. So this socialization activity is very important to change people's understanding regarding the causes and impacts of early marriage. This service activity was carried out using the socialization method and took place in the hall building with the Pringgabaya Utara village office. After conducting socialization, they believe that early marriage brings losses in terms of education, health and economics.